Analysis of E-Learning in Undergraduate Medical Education During Pandemic: Future Perspectives for Post-Covid Era - Devinta, Salzha; Wiyono, Nanang; Munawaroh, Siti; Hastami, Yunia (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2024)
The global Covid-19 pandemic has had a profound effect on medical education. Social distancing leads to the implementation and development of e-learning, especially in the medical education field. E-learning is an innovative learning method using technology that allows students to learn flexibly because learning materials are visualized in various formats that students easily access. This article uses the bibliometric analysis method. It is a quantitative method for analyzing bibliographic data of published articles from reputable sources using the VOSviewer app. We analyzed 949 high-quality research articles from the Scopus database on August 14, 2022. It shows that the publications related to the implementation of e-learning in medical education during the Covid-19 pandemic began to increase from 2020 to 2021 and decrease in 2022. Research that focuses on developing e-learning methods in undergraduate medical students needs to be conducted in the future as part of academic development for the medical education system. This research gives the future perspectives on the implementation of e-learning methods for post-covid era.This research also intended to help teachers and researchers to decide on suitable learning methods for medical education since the e-learning modality is beneficial not only for the pandemic era but also post-covid era. This study also discuss the impact of using e-learning in the learning domain of medical students in terms of knowledge, skills, and attitudes.